Attitude towards New Packaging to Reduce Condom-carrying Embarrassment among Thai Youth, A Cross-sectional Study - Apinut Wongkietkachorn; Kunathip Nissaipan; Narin Hiransuthikul (University Library System, University of Pittsburgh, 2014)
Background: Human Immunodeficiency Virus (HIV) incidence has been increasing in Thai youth, mostly from unsafe sex. Embarrassment with carrying condom was one of the main reasons. This study aims to evaluate attitude towards condom use, sexual behavior and the new condom packaging that merges with daily life products in Thai youth. Methods: A cross-sectional study was conducted among volunteers aged 15-24. New packaging were demonstrated and the volunteers were provided with questionnaires to complete in privacy booth and submit anonymously. Results: Of 680 participants with mean age of 19.7±2.7 years and 59.9% females, half of them thought condom should be carried and used. However, the same group did not actually do. Two-thirds of participants were interested and would use the packaging, citing these reasons charming, convenience, and disguise of condom. Females preferred the packaging significantly more than males. Conclusion: Disguising condom packaging, as phone charm and key ring, might be another safe and practical way to encourage youth to carry condoms around.